2014
DOI: 10.1589/jpts.26.1267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resistance Exercise Training to Strengthen Muscles across Multiple Joints of the Lower Limbs on Dynamic Balance Functions of Stroke Patients

Abstract: [Purpose] The objective of this study was to evaluate the effects of resistance exercise training for strengthening muscles across multiple joints on the dynamic balance function of stroke patients. [Subjects and Methods] Subjects in the training group (n=14) and the control group (n=14) received conservative physical therapy for 30 minutes per day, five days per week, for a period of six weeks. The training group additionally performed three sets (eight to 10 repetitions per set) of resistance exercise at 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Nine studies compared the effectiveness of different resistance training protocols in rehabilitation after stroke (Table 3, Figure S1). 26,28,29,41,45,[47][48][49][50] Participants and interventions: A total of 286 patients between three months and five years after acute incident were enrolled. About 12-40 training sessions were applied.…”
Section: Resistance Training Versus Other Resistance Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies compared the effectiveness of different resistance training protocols in rehabilitation after stroke (Table 3, Figure S1). 26,28,29,41,45,[47][48][49][50] Participants and interventions: A total of 286 patients between three months and five years after acute incident were enrolled. About 12-40 training sessions were applied.…”
Section: Resistance Training Versus Other Resistance Trainingmentioning
confidence: 99%
“…-Gait 26,29,41,45,[47][48][49][50] (Six Minute Walk Test, Ten Meter Walk Test, Timed Up and Go, Stair Climbing Power, fast, self-selected and habitual walking speed, plantar pressure distribution, swing phase duration). -Muscular force and motor function of lower limbs 26,41,45,[47][48][49] (isometric force, dynamic force, eccentric and concentric force of lower limb muscles (knee flexion and extension)).…”
Section: Resistance Training Versus Other Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…This exercise is able to activate leg muscles in a similar level compared to bodyweight exercises such as chair rise and hip thrust [ 27 ]. Moreover, it is found that chronic stroke patients not only gain strength on both affected and nonaffected legs but also have improvement in balance, walking ability, and functional performance [ 28 , 29 ].…”
Section: Review Of Training Activities Of Robots For Stroke Rehabimentioning
confidence: 99%
“…Different modalities of physical exercises already have well-established benefits for individuals after chronic stroke, including repercussions for cardiovascular capacity [2], muscle strength [3, 4], balance [5, 6], gait [7, 8], and cognition [9]. In order to maximize the effects of the exercises, there is a tendency to investigate the effects of multimodal protocols.…”
Section: Introductionmentioning
confidence: 99%